Social representations of history, cultural values, and willingness to fight in a war: A collective‐level analysis in 40 nations. Issue 4 (October 2016) - Páez, Darío; Liu, James H.; Bobowik, Magdalena; Basabe, Nekane; Hanke, Katja
Abstract : This study explores at the national level beliefs about world history and their relationship with cultural values and attitudes towards a national war. A country‐level analysis of university samples from 40 nations involving 7279 students showed that beliefs about history as a superior plan, as social progress, and lawful processes were positively associated with lower human development, and materialistic and power distance values, as well as with willingness to fight in a future national war. Further, beliefs about history as a superior plan, as social progress, and as lawful process were positively related with a stronger disposition to fight, even after controlling for cultural values and human development. Results are discussed in the framework of conceptualizing social representations of history as part of national political cultures.